Localization of Some Larval Stages of Schistosoma spp., in the Derna Waterfall, Libya - Ahmed Ekhnefer; Marfoua Ali; Zeinab Bofares; Fatma Agela (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Schistosoma, one of the Trematoda, is responsible for nearly 80,000 deaths per year. These worms cause the disease Schistosomiasis, which is the most common parasitic disease around the world. Studies on this topic in Libya were found to be very few, practically absent from the site of this study. In addition, lack of consciousness was a valid reason for us to study this topic; this study was aimed at tracing the stages of the life cycle of the Schistosoma worm and recording it in Derna waterfall. Methods. Random samples of water and mud from waterfall water was subjected for examining directly with a light microscope to search for miracidium phase. Meanwhile, samples of snails were gathered on the waterfall’s banks and categorized in an effort to locate the intermediate host. Stool and urine samples were collected from people living around the bank of the waterfall to search for eggs, and they were recorded. Blood samples from people living around the bank of the waterfall were collected and tested using a Schistosoma IgG ELISA to determine if they had antibodies against Schistosoma. Results. Miracidiam stage and eggs was found in water and mud samples in the study area, which indicates the presence of the adult phase. Results from snail samples confirm the presence of intermediate hosts of Schistosoma, including Biomphalaria and Bulins. Meanwhile, the presence of eggs and positive IgG was found among people living in the area of study. Conclusion. Results of this study recommend taking necessary measures include awareness of the population and the elimination of snails that are intermediate hosts of the worm, thus eliminating these worms.